Definición del denominado complejo ígneo básico en colombia y petrogénésis de su parte meridional (1980)
The Colombian Basic Igneous Complex is restricted at Colombian Western and it is composed by volcanic tholeiitic flows with some sedimentary rock intercalations. The age of that sequence ranges from Cretaceous through Tertiary and exhibits regional low grade metamorphism with zeolites and prehnite-pumpelleyte facies; the east edge is associated with continental plate deposits and related with the Romeral Fault System. The Complex exhibits basic and ultrabasic plutonism. There are two tectonic events in the geologic evolution of the complex; one of them is of Early Cretaceous time related to the interaction of oceanic and continental plate and the other is Later Cretaceous-Early Tertiary related with the colision of the island arc formed on the descendent oceanic plate. The development of ultramafic rocks seems different in each event, they go from Alpine type to Zonated with cummuIated and graded textures. Oceanic plagiogranites exists like tectonic inclusions within ultramafic rocks.  The Colombian Basic Igneous Complex is related with South America Northwestem Andean segment with different characteristics to the geological environment of the Central and Southern segments and could implie a different tectonic setting.